Generasi muda komuniti terpinggir ke arah penjanaan semula pembangunan generasi muda - Raja Suzana Raja Kasim; Samsudin A. Rahim (Penerbit UMK, Universiti Malaysia Kelantan, 2018)
This book examines the findings of a study from long-term research led by Universiti Malaysia Kelantan with nearly 6,000 young generations of marginalized communities in Malaysia. A series of interventions, face-to-face interviews and focus group discussions were carried out intensively that supported the results of the booked study. Through this book, inclusive, moderate and glorious models are translated through the inspiration and findings of studies that focus on outcomes for stakeholders. This book will share various new approaches in empowering the system and developing a positive young generation in various aspects.